(untitled) (Bulletin of criminological association of Ukraine, 2025)
The article states that since the beginning of the full-scale invasion, Ukraine has suffered unprecedented blows not only to civilian infrastructure, higher education institutions, unique domestic enterprises, but also to the environment. The provisions of the World Charter for Nature 1982 and the Rio de Janeiro Declaration on Environment and Development 1992 are considered. It is noted that currently, in the context of the consequences of a full-scale armed invasion, there is a need to rethink the provisions of these international documents, in particular, in the context of condemning not only the use of certain weapons that harm the environment, but also the methods and tactics of their application, in particular, in terms of the inadmissibility of targeted attacks on nuclear power plants, hydroelectric power plants, biosphere reserves, including attacks in the immediate vicinity of them, when the downing of a missile or drone by air defense forces can lead to irreparable consequences for nature and all of humanity. The admissibility of the possibility of committing ecocide not only in wartime, but also in peacetime is substantiated. The manifestations of ecocide in Ukraine in the context of a full-scale invasion are analyzed, in particular, the direct destruction of hydroelectric power plants and attempts to damage nuclear power plants (the explosion of the Kakhovka hydroelectric power plant by the Russian army in 2023); indirect consequences of rocket attacks, which include difficult access for the population to drinking water, proper sanitation, electricity, and deterioration of air quality.